Year-Round N2O Emissions From Long-Term Applications of Whole and Separated Liquid Dairy Slurry on a Perennial Grass Sward and Strategies for Mitigation - Hunt, Derek; Bittman, Shabtai; Chantigny, Martin; Lemke, Reynald (Frontiers in Sustainable Food Systems, 2019)
Dairy farms need to improve their environmental performance to justify continued consumption of dairy products. Previous studies have demonstrated improved re-use of dairy slurry nitrogen (N) and phosphorous (P) by separating solid and liquid fractions. This study was conducted to examine the long-term effects of applying whole dairy slurry (WS), separated liquid fraction (SLF), and mineral fertilizer on emission of nitrous oxide (N2O) from a grass sward in a moderate climate, and to identify methods to mitigate emissions. The results show that emission occurs in sharp spikes within a week of N application as well as after some wet/dry cycles and freeze/ thaw cycles even in this moderate climate. Greatest emissions occurred from late spring and summer applications. At the high application rate of total-N emissions were similar for WS and SLF, at the lower rate SLF exceeded WS, whereas at equivalent mineral-N, emissions were greater from WS than SLF. On the basis of crop N-uptake, SLF had similar or lower emissions than WS at comparable N rates, and the same was true on basis of yield except for lower emissions with WS than SLF at the low total-N rate (400 kg ha−1). By not finding pollution swapping, the study helps to support the use of slurry manure separation for its agronomic and environmental benefits. This multi-year field study supports current IPCC default values as cautious emission factors (EF) for dairy slurry and commercial fertilizer on intensively managed grass, though a lower EF may be justified for lower input grassland (<50 kg mineral-N ha−1 per dose). Our results suggest that N2O emissions can be reduced by transferring summer slurry application to early spring but on farms where this is not possible, mitigating summertime peaks should be targeted, possibly with the use of a nitrification inhibitor.